Special Issue 2024: Transforming Experience in Non-Hospital Settings - Patient Experience Journal (The Beryl Institute, 2023)
Patient Experience Journal(PXJ) is excited to announce the call for submissions for its July/August 2024 special issue focused on exploring how healthcare organizations are transforming experience in non-hospital settings. So much of the experience conversation has been focused on and driven by the hospital setting - from acute care, to pediatrics, safety net hospitals and more. While this focus remains essential to some of the most critical care delivered in the healthcare ecosystem, it is important to recognize the volume of care being provided in new and existing settings. This special issue seeks to uncover and elevate the practices happening in non-hospital settings and highlight research and evidence showing how efforts in these spaces is truly transforming the human experience in healthcare. These efforts can be the implementation of new programs or processes, research that tests new processes or programs, cases that share how organizations are working to elevate the experience they provide, be it in clinics or outpatient spaces, and even in people's homes. As the healthcare marketplace continues to dramatically shift, so too do the opportunities to ensure a conversation on experience is deeply rooted in these transformations. The reality is that as much as has been learned from and shared by the hospital setting, there is a vast expanse of organization experience and expertise that can advance the broader experience movement. We believe this issue can inspire just that.